Strategi Pengembangan Kawasan Kota Lama Sebagai Destinasi Wisata Sejarah Di Kota Kupang Provinsi Nusa Tenggara Timur - Maria Bernadetha Ringa; Noldi Mumu (Jurnal Inovasi Kebijakan, 2022)
Based on the background description, problem formulation, existing conditions, data analysis and results obtained, the research entitled The Strategy for the Development of the Old City Area as a Historical Tourism Destination, which aims to boost the economy in Kupang City, East Nusa Tenggara province, can be concluded: The old city area has at least 12 (twelve) historical sites that have the potential to be used as historical tourist destinations, however, currently, most of these tourist objects are in a state of disrepair.The results of data analysis and plotting of X, Y coordinates on the Cartesian Diagram, found that the position of historical sites in the Old City Area is located in quadrant I (first), which indicates that a strategy for developing these tourism objects is needed, namely: Aggressive Strategy, which focuses on efforts to regulate growth. This aggressive strategy must be the main and long-term strategy in the historical site development program for the Kota Lama area.